I exist, therefore the world thinks: Whitehead, Latour and scientific aesthetics - Araujo Pinho, Thiago (2023)
Many people think that the capacity for criticism and reflection, as well as the attitude of welcoming contingency, the other, and debate, is some internal and well-intentioned energy of open-minded people, as advocated by liberals, whether from the right or the left. What they don't realize is how much the capacity for reflection and dialogue is an external phenomenon, present in the world itself, produced only thanks to a space of resistances, encounters, and even frustrations, as in the academic and scientific sphere. It prevents my cogito and my precious epistemic schemes from getting out of control, in a dangerous transcendentalist delirium, and taking over the world and the circumstances themselves. The aim of this essay is precisely to understand this aesthetic dimension of science, this ontological feature that crosses its contours, taking as a starting point the concepts of "importance" in Whitehead and "matters of concern" in Bruno Latour.